Asthma Mortality in Canada, 1946 to 1990 - Robert S Hogg; Martin T Schechter; Julio SG Montaner; James C Hogg (Canadian Respiratory Journal)
OBJECTIVE: To assess the impact of asthma on Canadian mortality rates over a 45-year period.